2006
DOI: 10.1016/j.abb.2005.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic potential of sesquiterpene synthases: Alternative products of tobacco 5-epi-aristolochene synthase

Abstract: Nicotiana tabacum (tobacco) 5-epi-aristolochene synthase (TEAS) serves as an useful model for understanding the enzyme mechanisms of sesquiterpene biosynthesis. Despite extensive bio-chemical and structural characterization of TEAS, a more detailed analysis of the reaction product spectrum is lacking. This study reports the discovery and quantification of several alternative sesquiterpene products generated by recombinant TEAS in the single-vial GC-MS assay. The combined use of chiral and non-polar stationary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 31 publications
4
70
0
Order By: Relevance
“…[37] In some instances, these eudesmane hydrocarbons have been reported as co-products of reactions catalyzed by wild-type TEAS [38] and by mutants of aristolochene synthase. [4,39] Hz) and 19b (δ F =-183.90, J=48.9, 22.9 Hz) arise from axial/axial and axial/equatorial couplings to the protons on C2, in support of the 1α (axial) configurations of the fluoro substituents shown in Scheme 7.…”
Section: Acid-catalyzed Cyclizationsof Germacrene a And Fluorogermacrmentioning
confidence: 99%
“…[37] In some instances, these eudesmane hydrocarbons have been reported as co-products of reactions catalyzed by wild-type TEAS [38] and by mutants of aristolochene synthase. [4,39] Hz) and 19b (δ F =-183.90, J=48.9, 22.9 Hz) arise from axial/axial and axial/equatorial couplings to the protons on C2, in support of the 1α (axial) configurations of the fluoro substituents shown in Scheme 7.…”
Section: Acid-catalyzed Cyclizationsof Germacrene a And Fluorogermacrmentioning
confidence: 99%
“…However, in vitro testing has shown that several tomato TPSs from other clades that use trans-prenyl diphosphates in vivo are capable of using cis-prenyl diphosphate substrates in vitro (Falara et al, 2011), and some sesquiterpene synthases from tobacco can use cis-trans FPP in addition to all-trans FPP as substrates (O'Maille et al, 2006). More recently, a CPT gene that catalyzes the head-to-middle condensation of two DMAPP molecules to produce lavendulyl diphosphate has been described in lavender (Lavendula x. intermedia) (Demissie et al, 2013).…”
Section: Online)mentioning
confidence: 99%
“…In other examples, taxadiene synthase catalyzes the cyclization of 6-fluorogeranylgeranyl diphosphate to generate a mixture of 7-fluoroverticillenes [39], and aristolochene synthase catalyzes the cyclization of 2-fluorofarnesyl diphosphate to form 2-fluorogermacrene A [40]. 5-Epi-aristolochene synthase, for which the stereochemical details of the cyclization mechanism have been recently outlined [41], generates 25 sesquiterpene products [42], and mutagenesis studies targeting evolutionarily variable residues in and surrounding the active site show that product arrays can be altered by design [43].…”
Section: Cyclization Reactionsmentioning
confidence: 99%